After the first 32 years - new deal in Hungarian income taxation - Lakatos, Maria; Karai, Éva (Anali Ekonomskog fakulteta u Subotici, 2020)
Nowadays, few experts or politicians look back to the 80s, the post-communist countries present their results after the transition to a market economy. But in the 1980s Hungary, was the first of the socialist countries to launch major reforms, and within that, the financial system has been reformed. The conversion of the banking and the insurance system started at that time, parallel with the Németh government fundamentally overturned the tax system and laid the foundations of today’s modern tax system in both of direct and indirect taxation. Our study reviews the period that has been pasted from 1988 till the present time, but emphasizes only one question, what is the link between government tax policy implemented in tax legislation and the behavior of taxpayers.